REVERSE LOGISTICS OF MEDICINES IN BRAZIL: an contribution to sustainability - Mamédio da Silva, Geisa; Oliveira, André Luiz (Revista Interface Tecnológica, 2020)
The National Solid Waste Policy (PNRS), which establish guidelines for the correct disposal of waste, is still not respected efficiently, proof of this is the large amount of waste disposed of incorrectly in the environment every day, causing negative impacts. The incorrect disposal of medicines has been a major problem. Within this context, implementing reverse logistics is an important strategy to promote sustainability and thus cause less problems to the environment. The aim of this study is to highlight the process of reverse drug logistics as a factor aimed at promoting sustainable development. The methodology used to prepare the article was Literature Review. Articles, theses, monographs, documents published in symposia and magazines were consulted, whose theme was the focus of this study. The researched literature shows the importance for the environment of the correct disposal of any solid waste, and in view of the fact that the medicines are chemical compounds, this disposal is even more necessary, because in addition to impacting the environment, the medicines can bring serious damages to Cheers. Therefore, the reverse logistics of medicines contributes positively to make sustainable development a tangible reality.